2018
DOI: 10.1002/oby.22251
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Mortality in Mexican American Adults: Results from the National Health and Nutrition Examination Survey

Abstract: Waist circumference and WHtR were associated with increased risk of all-cause and diabetes-related mortality in US-residing Mexican American adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“… 35 36 Ultimately, 72 prospective cohort studies with 2 528 297 participants and 150 164 events were included in final analyses. 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 Thirty studies were from Europe, 22 studies were from the United States, 16 studies were from Asia, two studies were from Canada, one from Brazil, and one from Tobago in South America. Twelve studies included only men, 12 studies included only women, and another 48 studies included both sexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 36 Ultimately, 72 prospective cohort studies with 2 528 297 participants and 150 164 events were included in final analyses. 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 Thirty studies were from Europe, 22 studies were from the United States, 16 studies were from Asia, two studies were from Canada, one from Brazil, and one from Tobago in South America. Twelve studies included only men, 12 studies included only women, and another 48 studies included both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Three different publications from the third National Health and Nutrition Examination Survey were included in the analyses of waist-to-height ratio,59 thigh circumference,102 and waist circumference, waist-to-hip ratio, and waist-to-thigh ratio 86. Another publication from this study that reported direct estimations for one standard deviation increment in anthropometric measures was included in the analyses of standard deviations 63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have shown that WC has been positively associated with CVDs, all-cause mortality, and new-onset T2DM [21][22][23][24][25], it has rarely been studied among patients with T2DM. Sone et al found-in a relatively small cohort study-that a high WC value alone is not sufficient to raise the risk of CVD events significantly and is not an independent risk factor in Japanese diabetic patients [26].…”
Section: Introductionmentioning
confidence: 99%
“…Within similar BMI, increased muscle mass is associated with increased insulin sensitivity and better metabolic profile. Increased waist circumference and waist to hip ratio (that have been shown to be good surrogate markers for adiposity) are associated with increased mortality in specific ethnicities like Mexican Americans [ 35 ]. Prior studies have also shown that fasting insulin levels, HDL cholesterol as well as triglyceride levels are independently related to body fat percent and waist to hip ratio [ 36 ].…”
Section: Discussionmentioning
confidence: 99%